(untitled) (Eurasian Research Bulletin, 2023)
The observed patients were divided into 2 groups: the 1st group consisted of 20 children aged from 10 days to 1.5 months; Group 2 included 65 children aged 1.5 to 5 months. 50 children were breast-fed, artificial (children received adapted mixtures "Detolact", "Nutrilak", "NAS") - 15 children. The predominant class of immunoglobulins in the blood serum of the examined children was immunoglobulin G. Its concentration in children of the first age group was -5.75 ± 0.26 g/l. The content of immunoglobulin M in the blood serum of the observed children (in the 1st group - 0.83 ± 0.05 g/l; in the 2nd group - 0.99 ± 0.05 g/l) was significantly higher than in healthy children (0.32 ± 0.14 g/l and 0.48 ± 0.16 g/l, respectively; p <0.01). The same changes were observed in the concentration of class A immunoglobulin (in the 1st group, 26 ± 0.05 g/l, in the 2nd group - 0.39 ± 0.03 g/l, in healthy children, the IgA content was 0 0.07 ± 0.05 g/l and 0.15 ± 0.10, p><0.01). >